Designing multifunctional MOFs using an inorganic motif [Cu3(μ3-OH)(μ-Pyz)] as SBU and their properties - Akhtar, S.; Bala, S.; De, A.; Das, K. S.; Adhikary, A.; Jyotsna, S.; Poddar, P.; Mondal, R. (Crystal Growth & Design, 2019)
In a continuation of our interest in pyrazole-based multifunctional metal-organic frameworks (MOFs), we report herein the construction of a series of Cu(II) MOFs using pyrazole and various 5-substituted isophthalic acids. The central theme is to generate MOFs using the crystal engineering strategy of spacer and node; however, for the node we have introduced a well-known inorganic motif, a [Cu-3(mu(3)-OH)(mu-Pyz)(3)] unit. The appearance of the SBU in five MOFs confirms the robustness and reproducibility of the motif with some interesting structures of various dimensionality ranging from 1D helical and 2D herringbone grid to a complex 3D framework. The deployment of bent acids brings chirality via helicity in the system, as further confirmed by solid-state CD spectra. A detailed investigation of the porous MOFs reveals their importance as zeolite analogues for environment remediation. MOF-1-MOF-5 show some interesting photodegradation of harmful organic dyes. MOF-4 and MOF-5 show impressive selective CO2 gas sorption properties. Furthermore, magnetic properties associated with the trinuclear and hexanuclear SBUs of MOF-1 and MOF-3-MOF-5 have also been investigated.